Differences in PAR-2 activating potential by king crab (Paralithodes camtschaticus), salmon (Salmo salar), and bovine (Bos taurus) trypsin. - Larsen, Anett Kristin; Kristiansen, Kurt; Sylte, Ingebrigt; Seternes, Ole Morten; Bang, Berit (BMC Research Notes, 2013)
The manuscript version of this article, under a different title, is paper 3 of Anett Kristin Larsen's doctoral thesis which is available in Munin at http://hdl.handle.net/10037/2892 Background: Salmon trypsin is shown to increase secretion of the pro-inflammatory cytokine interleukin (IL)-8 from human airway epithelial cells through activation of PAR-2. Secretion of IL-8 induced by king crab trypsin is observed in a different concentration range compared to salmon trypsin, and seems to be only partially related to PAR-2 activation. This report aim to identify differences in the molecular structure of king crab trypsin (Paralithodes camtschaticus) compared to salmon (Salmo salar) and bovine trypsin (Bos taurus) that might influence the ability to activate protease-activated receptor-2 (PAR-2). Results: During purification king crab trypsin displayed stronger binding capacity to the anionic column used in fast protein liquid chromatography compared to fish trypsins, and was identified as a slightly bigger molecule. Measurements of enzymatic activity yielded no obvious differences between the trypsins tested. Molecular modelling showed that king crab trypsin has a large area with strong negative electrostatic potential compared to the smaller negative areas in bovine and salmon trypsins. Bovine and salmon trypsins also displayed areas with strong positive electrostatic potential, a feature lacking in the king crab trypsin. Furthermore we have identified 3 divergent positions (Asp196, Arg244, and Tyr247) located near the substrate binding pocket of king crab trypsin that might affect the binding and cleavage of PAR-2. Conclusion: These preliminary results indicate that electrostatic interactions could be of importance in binding, cleavage and subsequent activation of PAR-2.